Capacitación tributaria para pequeñas y medianas empresas (pymes) en el cantón La Maná provincia de Cotopaxi - Cusco Zambrano, Liseth Tatiana (2016)
This research work was aimed for the purpose of implementing a tax training program for small and medium enterprises (SMEs) in cantón La Maná; in order to know the current situation in their tax and general aspects regarding the knowledge and application of the tax legislation, for which a SWOT analysis was performed; for gathering information from primary sources, a survey was applied to the owners of small and medium enterprises in the canton, this procedure allowed to detect that there is 45% of ignorance in the implementation and fulfillment of their tax obligations, therefore it poses a model training is posed where the shape of the for management, RISE, RUC, DIMM online statements, practical exercise of forms, invoices practical exercise, management system online, tax reconciliation.